Impact of COVID-19 on nursing professionals' mental health (Research, Society and Development, 2023)
During the COVID-19 pandemic, a global emergency responsible for over 6.63 million deaths, it represented a large-scale infectious public health event that was responsible for radically changing the structures and investments of health systems. Facing this scenario of fragilities, the mental health of health professionals has gained prominence among the concerns. Therefore, the present article aims to discuss and describe, through literature review, the impacts of the pandemic of COVID-19 on the mental health of nursing professionals, understanding the psychological impact generated in these professionals. This is an integrative literature review by searching the databases PUBMED, Scielo and BVS. Articles published between 2020 and 2022, and that answered the research question were included. In the end, a sample of 16 articles was obtained. The main symptoms reported among these professionals were depression, discouragement, anxiety, worry, insomnia, and stress. Moreover, it was identified that the symptoms of depression are related to smoking, years of work, hospital characteristics, work sectors, and direct contact with the patient. Thus, it is noted that the impact generated by COVID-19 on the mental health of nursing professionals has become a serious public health problem, thus, the present study reinforces the need for further studies in order to generate an impact on health services, demonstrating the need to offer care to the caregiver, especially in the area of mental health.